Complete measurements of anisotropic x-ray emission following recombination of highly charged ions. (August 2015) - Shah, Chintan; Amaro, Pedro; Steinbrügge, René; Beilmann, Christian; Bernitt, Sven; Fritzsche, Stephan; Surzhykov, Andrey; López-Urrutia, José R Crespo; Tashenov, Stanislav
Synopsis: We report the first systematic measurement of x-ray emission anisotropies following dielectronic, trielectronic and quadroelectronic recombination into He-like through O-like iron and krypton ions. Using the experimental data we calculated the polarization of the Kα x rays in an anisotropic plasma as a function of the plasma temperature. Unexpectedly, we found that the degree of polarization is dominated by previously neglected trielectronic and quadroelectronic recombination resonances.